Cytokine storm-calming property of the isoquinoline alkaloids in Coptis chinensis Franch - Lan, Yuejia; Wang, Huan; Wu, Jiasi; Meng, Xianli (Frontiers in Pharmacology, 2022)
Coronavirus disease (COVID-19) has spread worldwide and its effects have been more devastating than any other infectious disease. Importantly, patients with severe COVID-19 show conspicuous increases in cytokines, including interleukin (IL)-6, monocyte chemoattractant protein (MCP)-1, IL-8, tumor necrosis factor (TNF)-α, IL-1, IL-18, and IL-17, with characteristics of the cytokine storm (CS). Although recently studied cytokine inhibitors are considered as potent and targeted approaches, once an immunological complication like CS happens, anti-viral or anti-inflammation based monotherapy alone is not enough. Interestingly, certain isoquinoline alkaloids in Coptis chinensis Franch. (CCFIAs) exerted a multitude of biological activities such as anti-inflammatory, antioxidant, antibacterial, and immunomodulatory etc, revealing a great potential for calming CS. Therefore, in this timeline review, we report and compare the effects of CCFIAs to attenuate the exacerbation of inflammatory responses by modulating signaling pathways like NF-ĸB, MAPK, JAK/STAT, and NLRP3. In addition, we also discuss the role of berberine (BBR) in two different triggers of CS, namely sepsis and viral infections, as well as its clinical applications. These evidence provide a rationale for considering CCFIAs as therapeutic agents against inflammatory CS and this suggestion requires further validation with clinical studies.